The Relationship of Human Resources Recruitment System in Improving Employee Performance in Hospital Administrative Units - Devi Pramita Sari; Ilyas Syafiq Darul Ridzuan; Nadia Nawangsih (Global Health Science Group, 2023)
Hospitals are said to be of good quality as evidenced by the performance of hospital administrative officers in hospital services which are supported by a good human resource recruitment system. Based on the preliminary survey, it is known that there are 2 hospital administration officers who have good performance. The purpose of this study was to determine the relationship between the human resource recruitment system in improving employee performance in the hospital administrative unit. The object of this research is the hospital administration unit. The research used descriptive and quantitative methods and a cross sectional study approach. The population and research samples were taken by total sampling, namely all hospital administration officers at Tunas Harapan Salatiga Hospital as many as 9 respondents. The research instrument used a questionnaire. Quantitative data analysis used the chi-square relationship test. The results of this study were 9 respondents based on the results of the Chi-Square test the significance of the p anatara independent variables, namely the human resource recruitment system with the dependent variable increasing employee performance, the results obtained were 0.03 (p <0.05). Ho was rejected and stated there was a relationship. The conclusion is that there is a relationship between the human resource recruitment system in improving employee performance in the hospital administration unit. Suggestions that the Human Resources department should motivate and update the knowledge of hospital administrative officers to conduct training and it is hoped that for further research, conduct research on all units in the hospital.